Changing communities - Harding, Ben; Oliver, Paul; Garner, Simon; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2005)
Every community experiences change, whether it be the result of cultural, economic or sosial forces. In this program, we examine what changes have occured and the reasons for them, getting to know some of the major players who are leading the community into the future.
Title from title screen.
Executive producer, Mark McAuliffe ; editor, Paul Oliver ; graphic, Raquel Solier ; sound, Wayne Martin, Alexy Gudimenko ; camera, Max Davis, Zane Lovitt, Jared Marshall.
Presenter: Karen Appathurai.
Keywords: Communities; Social change; Economic development